Conceptual provisions of communication management in the conditions of development of industrial enterprises - Bezchasnyi, Oleksii (Skhid, 2019)
In the article the concept of communication management under the development conditions of industrial enterprises is developed, which contains the substantiation of the solution of the problem of improvement of the communication system of the industrial enterprise, namely: choice of basic theories and assumptions; methods to be applied; requirements for tools to solve the problem and to ensure that the recommendations developed are put into practice. Through the use of the concept in the management of an industrial enterprise, a balanced improvement of the communication system is ensured, taking into account the development goals of the enterprise. The scheme of communication management system under development conditions of industrial enterprises is offered, which takes into account the peculiarities of communications of a typical industrial enterprise and the classification of management objects depending on the directions of communication they carry out and on their position in the enterprise management system. Using the scheme of communication management system under the development conditions of industrial enterprises increases the theoretical validity of industrial enterprise management and reduces losses from the negative effects of the external and internal environment.